Thin layer drying of hybrid rice seed - Hasan, A. A. M.; Bala, B. K.; Kamal, Md Rowshon (Elsevier, 2014)
This paper presents thin layer drying characteristics of hybrid rice seed and quality of the dried rice seed in terms of germination capacity and colour. Thin layer drying of hybrid rice seed was conducted at the temperature levels of 40 °C, 50 °C and 60 °C, relative humidity ranging 10 to 15% and air velocity ranging 0.55 to 0.65 m/s. Drying rate increases with the increase in drying air temperature and the drying air temperature has a significant effect on the seed quality. Five thin-layer drying models were fitted to the experimental data of thin layer drying of hybrid rice seed. Midilli equation was found to be the best followed by two term exponential equation, Page equation, Henderson and Pabis equation and Newton model. The agreement between the predicted and experimental results was excellent. Germination capacity was the highest for the drying air temperature of 40 °C and then it decreased significantly with the increase of drying air temperature above 40 °C. Colour of the hybrid rice seed did not change with the increase of drying temperature. Lightness, hue angle and chroma were found to be almost same for these three drying air temperatures. It is recommended that hybrid rice seed should not be dried above 40 °C.